How to house the homeless - Ellen, Ingrid Gould, 1965-; O'Flaherty, Brendan (Russell Sage Foundation, 2010)
Elucidates for the link between homelessness and housing policy, assesses the current state of affairs, analyzes promising policies and programs, and offers a new agenda for future research.